The Transantral Endoscopic Approach: A Portal for Masses of the Inferior Orbit—Improving Surgeons' Experience Through Virtual Endoscopy and Augmented Reality - Tel, Alessandro; Arboit, Lorenzo; Sembronio, Salvatore; Costa, Fabio; Nocini, Riccardo; Robiony, Massimo (Frontiers in Surgery, 2021)
In the last years, endoscopic techniques have raised an increasing interest to perform minimally invasive accesses to the orbit, resulting in excellent clinical outcomes with inferior morbidities and complication rates. Amongst endoscopic approaches, the transantral endoscopic approach allows to create a portal to the orbital floor, representing the most straightforward access to lesions located in the inferior orbital space. However, if on the one side endoscopic surgery provides enhanced magnified vision of the anatomy in a bloodless field, on the other side has several impairments compared with classic open surgery, owing to restricted operative spaces. Virtual surgical planning and anatomical computer-generated models have proved to be of great importance to plan endoscopic surgical approaches, and their role can be widened with the integration of surgical navigation, virtual endoscopy simulation and augmented reality. This study focuses on the strict conjugation between the technologies that allow the virtualization of surgery in an entirely digital environment, which can be transferred to the patient using intraoperative navigation, or to a printed model using augmented reality for presurgical analysis. Therefore, the interaction between different software packages and platforms offers a highly predictive preview of the surgical scenario, contributing to increase orientation, awareness and effectiveness of maneuvers performed under endoscopic guidance, which can be checked at any time using surgical navigation. In this paper the Authors explore the transantral approach for the excision of masses of the inferior orbital compartment through modern technology. The Authors apply this technique for masses located in the inferior orbit and share their clinical results, describing why technological innovation, and, in particular, computer planning, virtual endoscopy, navigation and augmented reality can contribute to empower minimally invasive orbital surgery, at the same time offering a valuable and indispensable tool for presurgical analysis and training.